Theoretical Approaches to the Collection and Appraisal of Graffiti Ephemera: A Toronto, Ontario, Case Study - Cunningham Rogers, Al (Archivaria)

(untitled) (Association of Canadian Archivists, 2024)
This article explores aspects of the archival value of graffiti and street art. It applies an intersectional feminist lens and draws upon Althusserian subject interpellation to elaborate some potential techniques for appraising graffiti. Understanding graffiti as ideological calls can help us understand how graffiti acts on us and functions for us: as a record of oppression, institutional and social relations, and individual negotiations with power. The article offers examples of graffiti acting as a form of speech for the unheard and marginalized and illustrates these examples with photographs of graffiti captured by the author and images of graffiti and street art located in various collections. It compares the appraisal and collection methods of the Urban Art Mapping Project, a North American participatory graffiti archive, with the Street- ARToronto (StART) street-art map maintained by the City of Toronto. Through these comparisons, the article argues for the evidential value of locally driven archives of the type of political graffiti excluded from the StART map.